2021
DOI: 10.1155/2021/3960553
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Discectomy and Fusion Using Zero-P System for Treatment of Cervical Spondylosis: A Meta-Analysis

Abstract: Objective. The current study aimed to explore the efficacy of Zero profile intervertebral fusion system (Zero-P) and traditional anterior plate cage system (PC) in the treatment of cervical spondylotic myelopathy (CSM). Further, the present study evaluated effects of the treatments on medical security, height of intervertebral disc, adjacent-level ossification development (ALOD), and adjacent segmentation disease (ASD) through a systematic retrospective analysis. Methods. Studies on Zero-P system and tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Five patients (12.8%) who underwent the anterior approach had transient dysphagia one week postoperatively but recovered after subsequent treatment. Based on the incidence of 904 patients in the meta-analysis of Guo et al, our incidence was similar to the 13.97% of zero-p and lower than the 26.01% of plate-cage [ 10 ]. This suggests that Low-P can achieve a similar effect to zero-p in reducing the incidence of postoperative dysphagia.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Five patients (12.8%) who underwent the anterior approach had transient dysphagia one week postoperatively but recovered after subsequent treatment. Based on the incidence of 904 patients in the meta-analysis of Guo et al, our incidence was similar to the 13.97% of zero-p and lower than the 26.01% of plate-cage [ 10 ]. This suggests that Low-P can achieve a similar effect to zero-p in reducing the incidence of postoperative dysphagia.…”
Section: Discussionmentioning
confidence: 79%
“…However, a higher number of surgical levels, high-profile internal fixation, and prolonged muscle traction may lead to a higher rate of cage subsidence and nonunion, as well as a higher incidence of dysphagia [ 4 , 5 , 7 ]. Zero-profile cages have been trialed in MDCM, which help reduce the risk of developing dysphagia, but higher-risk cage subsidence rates and cervical alignment problems must be considered [ 8 , 9 , 10 ]. Posterior cervical laminectomy and instrumented fusion (PCLF) can achieve indirect decompression by causing the spinal cord to drift posteriorly and is mostly used in patients with MDCM [ 1 , 3 , 11 ], but the widely used traditional lateral mass screw fixation is not very stable and does not provide satisfactory correction of kyphosis [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, as both techniques rely on cage or graft insertion, our meta-analysis found no difference between SAAS and APC in restoring disc height. 50 It has been reported that primary ACDF showed a fusion rate of 92-95% in treating primary cervical pathologies such as spondylosis or trauma. 51,52 Guo et al, 50 on the other hand, found lower but comparable fusion rates between APC and SAAS groups, with rates of (173/199 = 86.9%) and (156/184 = 84.8%), respectively.…”
Section: Radiological Outcomesmentioning
confidence: 99%
“…50 It has been reported that primary ACDF showed a fusion rate of 92-95% in treating primary cervical pathologies such as spondylosis or trauma. 51,52 Guo et al, 50 on the other hand, found lower but comparable fusion rates between APC and SAAS groups, with rates of (173/199 = 86.9%) and (156/184 = 84.8%), respectively. Chen et al 53 reviewed 63 patients who underwent ACDF with SAAS for ASDis and found a 2-year fusion rate of 95.2%.…”
Section: Radiological Outcomesmentioning
confidence: 99%
“…However, Park et al (2019) conducted a retrospective cohort study on discectomy and found that multi-level fusion was significantly associated with the increased risk of screw failure (p < 0.01). Screw loosening and plate migration in the anterior cervical discectomy fusion (ACDF) is not rare (Ning et al, 2008;Guo et al, 2021), even though hardware failure attributed to ACDF was demonstrated only 0.1%-0.9% in the United States (Epstein, 2019). Many clinical case reports revealed that screw loosening and anterior cervical plate migration happened in ACDF (Azadarmaki and Soliman, 2014;Nathani et al, 2015;Wójtowicz et al, 2015;Fryer et al, 2019;Ansari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%